Effect of Intermittent Deep Fat Frying Cycles on the Flavor and the Formation of Polycyclic Aromatic Hydrocarbons in Fried Chicken Drumsticks - JIN Long, HUANG Dewei, CHENG Huilin, LIU Yue, HU Yingying, ZHANG Lang, XU Baocai (Shipin Kexue)
This study investigated the impacts of different intermittent deep fat frying cycles on the physiochemical properties, flavor, and polycyclic aromatic hydrocarbons (PAHs) of fried chicken drumsticks. The results indicated that as frying cycles increased, the water content and L* value of fried chicken drumsticks decreased (P 0.05). The peroxide value (POV) and thiobarbituric acid reactive substances (TBARS) content of soybean oil increased with the increase in the number of frying cycles (P < 0.05). Eighty-one volatile compounds were detected in all samples, and the total PAHs level in fried chicken increased from 21.44 to 33.55 ng/g as the number of frying cycles increased one to five (P < 0.05). Additionally, correlation analysis indicated that the generation of PAHs had a positive correlation with fat oxidation and pyrazine levels but a negative correlation with hydrocarbon levels. The findings provide a theoretical basis for controlling PAHs formation and improving the quality properties of deep-fried meat products.